Chordomas: long-term results of postoperative irradiation. Prognostic factors - Pluta, Elżbieta; Gliński, Bogdan; Ząbek, Magdalena; Urbański, Jacek; Krzemieniecki, Krzysztof; Frączek-Błachut, Beata; Mucha-Małecka, Anna; Szpytma, Teresa (Contemporary Oncology/Współczesna Onkologia, 2006)
Aim of the study: To determine the value of postoperative radiotherapy in patients with chordoma and to identify the prognostic factors. Materials and methods: Twenty-two patients with chordoma were irradiated in Cracow Oncological Center in the period 1975-2000. All patients underwent primary surgery and 10 of them were operated on non-radically. Inoperable recurrence was an indication in the next 12 cases. Telegammatherapy or photon beams from linear accelerator were used, and the total dose delivered ranged from 48 to 60 Gy with conventional fractionation 200 cGy per day. Results: Tolerance to the treatment was good. Ten-year actuarial overall survival (AOS) in the whole group of 22 patients was 28%. A Cox multivariate analysis revealed that tumour location was the single, independent prognostic factor. Ten-year AOSs for intracranial and vertebral locations were 68% and 11% respectively. Univariate analysis indicated better prognosis for women than for man; also patients under 40 years of age carried better prognosis than older. Ten-year AOSs were 56%, 14% and 58%, 15%, respectively. Conclusions: Postoperative radiotherapy offers long-term survival in 28% of irradiated patients with chordoma, and the best prognosis refers to the intracranial tumour location.